Collocations of high frequency words in nursing research articles and The Academic Collocation List: Similarities and differences - Kaja Mandić; Izabela Dankić (ExELL (Explorations in English Language and Linguistics))
The main objective of this corpus-based study is to research the most frequent two-word collo-cations in the corpus of nursing scientific articles and compare this newly assembled list of nursing collocations with the Academic Collocation List (ACL). The nursing scientific articles corpus (NSAC) used in this study comprises 1,119,441 words from 262 articles of 10 high-quality journals from the Medical Library Association list which nursing students can freely access. The focus is on noun-noun and noun-adjective collocations. The selected articles were converted into txt files using the ABBYY Fine Reader. WordSmith Tools 7.0 and TermeX were used for noun and collocation extraction. The newly assembled Nursing Collocation List (NCL) and the ACL were compared using Microsoft Excel 2016. A total of 488 collocations were identified in the NSAC and the NCL contains 234 (47.9%) noun + noun and 254 (52.1%) adjective + noun collocation combinations. The most frequent two-word collocation is health care and it appeared 618 times in the NSAC. The ACL (2,469) and the NCL (488) share 123 two-word collocations. Although there are some correspondences between collocations in the two corpora, key nursing collocations with notably higher frequencies are identified in the NSAC (365). Despite the fact that the ACL is the most extensive collocation list across different academic fields and it certainly plays an important role in teaching English as a foreign language, this study suggests that it does not provide key nursing collocations for improvement of nursing collocation competence.